Adult‐Onset Neurodegeneration in Nucleotide Excision Repair Disorders (NERDND): Time to Move Beyond the Skin. Issue 8 (14th June 2022) - Cordts, Isabell; Önder, Demet; Traschütz, Andreas; Kobeleva, Xenia; Karin, Ivan; Minnerop, Martina; Koertvelyessy, Peter; Biskup, Saskia; Forchhammer, Stephan; Binder, Johannes; Tzschach, Andreas; Meiss, Frank; et al.
ABSTRACT: Background: Variants in genes of the nucleotide excision repair (NER) pathway have been associated with heterogeneous clinical presentations ranging from xeroderma pigmentosum to Cockayne syndrome and trichothiodystrophy. NER deficiencies manifest with photosensitivity and skin cancer, but also developmental delay and early‐onset neurological degeneration. Adult‐onset neurological features have been reported in only a few xeroderma pigmentosum cases, all showing at least mild skin manifestations. Objective: The aim of this multicenter study was to investigate the frequency and clinical features of patients with biallelic variants in NER genes who are predominantly presenting with neurological signs. Methods: In‐house exome and genome datasets of 14, 303 patients, including 3543 neurological cases, were screened for deleterious variants in NER‐related genes. Clinical workup included in‐depth neurological and dermatological assessments. Results: We identified 13 patients with variants in ERCC4 (n = 8), ERCC2 (n = 4), or XPA (n = 1), mostly proven biallelic, including five different recurrent and six novel variants. All individuals had adult‐onset progressive neurological deterioration with ataxia, dementia, and frequently chorea, neuropathy, and spasticity. Brain magnetic resonance imaging showed profound global brain atrophy in all patients. Dermatological examination did not show any skin cancer or pronounced ultraviolet damage. Conclusions: We introduce NERDND as adult‐onset neurodegeneration (ND ) within the spectrum of autosomal recessive NER disorders (NERD). Our study demonstrates that NERDND is probably an underdiagnosed cause of neurodegeneration in adulthood and should be considered in patients with overlapping cognitive and movement abnormalities. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.